Desempenho agronômico do cártamo submetido à compactação do solo e adubação nitrogenada em latossolo vermelho - Ferreira, Pamela Palhano (2016)
The safflower is an alternative to the high quality oil production, one of the economic options for cropping systems. The compaction and low soil fertility are factors that can limit crop production. So the objective was to evaluate the agronomic performance of safflower crop, generating information about the interaction of soil density levels and nitrogen levels in Oxisol red. The experiment was conducted in a greenhouse at the Federal University of Mato Grosso, Campus Rondonopolis, the soil was the Oxisol, collected at a depth of 0-20 cm in native Cerrado. The experimental design was a randomized block in a factorial fractionated 5x5, corresponding to five levels of compaction (soil densities: 1,0; 1,2; 1,4; 1,6 and 1,8 Mg m-3) and five nitrogen fertilization rates (0; 50; 100; 150; and 200 mg dm-3) with four repetitions, totaling 52 experimental units. Before sowing the soil was fertilized with micronutrients at a dose of 30 mg dm-3, phosphorus and potassium both at a dose of 300 mg dm-3, nitrogen was installments, with the first application at planting and the second 30 days after the emergency. The evaluations were made at 30, 60 and 83 days after emergence. The variables analyzed were plant height, stem diameter, number of leaves, dry weight of shoot, diameter and dry matter chapter, root development (in each layer of the experimental unit), SPAD reading (indirect measurement of content chlorophyll), concentration and accumulation of nitrogen, soil density and porosity. The results were submitted to variance analysis and when significant to the use of regression study with significance 5% probability. There was no interaction of soil density combinations and doses of nitrogen in safflower cultivation in Oxisol Red with isolated effect for both factors. Soil compaction in the subsurface damaged the growth of safflower crop reducing plant height, leaf number, the number of chapters, dry mass of the aerial part, the chapters and roots, also reduced the accumulation of nitrogen in the shoot and chapters, reduced the total porosity. Nitrogen fertilization increased chlorophyll content, the concentration and accumulation of nitrogen in the shoot and in the chapters. The volume of root per layer and the total was reduced by both the density and the nitrogen fertilization.